Digital Transformation in Education: A Study of Technology Implementation at SMA Negeri 5 Makassar City - Shaleh Alwi, Andi Muhammad (International Journal on Advanced Science, Education, and Religion, 2024)
Digital transformation in education has become an essential need to improve the effectiveness of learning. This study aims to analyze the implementation of digital technology in SMA Negeri 5 Makassar City in supporting the learning process. The research method used is a qualitative method with a case study approach. Data were collected through interviews, observations, and documentation. The results of the study indicate that the use of digital technology such as the Learning Management System (LMS), online learning applications, and other digital devices can improve interaction between teachers and students, and provide flexibility in the teaching and learning process. However, challenges such as limited infrastructure and readiness of educators are still major obstacles. Therefore, strategic policies are needed from schools and the government in optimizing the application of digital technology in education.